PENGGUNAAN RAGI ROTI (SACCHAROMYCES CEREVICIAE) DALAM PAKAN UNTUK MENINGKATKAN RESPON KEKEBALAN NON-SPESIFIK PADA IKAN NILA (OREOCHROMIS NILOTICUS) - Reo C; Nikodemus Dahoklory; Kiik G. Sine (Nusa Cendana University, 2018)
Abstract - This research to seeing the effect of bread yeast (Saccharomyces cereviciae) in improving the respons non-specific immunity in tilapia (Oreochromis niloticus). Tilapia with an average weight of 31.83 g is maintain in five aquariums with a density of 5 tails per aquarium. Fish fed with pellets mixed with breat yeast in accordance with the treatment of treatment A (control), treatment B (10 g / kg pellet), treatment C (20 g / kg pellet), treatment D (30 g / kg pellet) and treatment E (40 g / kg of pellets). Feed is given in accordance to the dose of 5% with the frequency of feeding 2 times a day ie Morning and Afternoon. The result of ANOVA show that giving bread yeast into pellet feed as much as 10 g had an effect on total leucocytes, phagocytosis activity and absolute growth. Keywords : Tilapia, Yeast Bread, Leucocytes, Phagocytosis, Growth